Multi-leader multi-follower model with aggregative uncertainty - Lina Mallozzi; Roberta Messalli (Games, 2017)
We study a non-cooperative game with aggregative structure, namely when the payoffs depend on the strategies of the opponent players through an aggregator function. We assume that a subset of players behave as leaders in a Stackelberg model. The leaders, as well the followers, act non-cooperatively between themselves and solve a Nash equilibrium problem. We assume an exogenous uncertainty affecting the aggregator and we obtain existence results for the stochastic resulting game. Some examples are illustrated.
Keywords: 330; aggregative game; hierarchical model; Nash equilibrium